Camouflaged Animals - "Duprez, Martine" (Belitha press: London, 1994)
Every animal has a unique part to play in maintaining nature's balance. This book, which is one of a series looks at the role of various animals in the natural world, presents a wide range of creatures which are masters of disguise and shows the subtle way in which they conceal themselves.